Efficacy and safety of rituximab in peripheral ulcerative keratitis associated with rheumatoid arthritis. Issue 1 (28th January 2021) - Bonnet, Isabelle; Rousseau, Antoine; Duraffour, Pierre; Pouchot, Jacques; Nguyen, Chi Duc; Gabison, Eric; Seror, Raphaele; Marotte, Hubert; Mariette, Xavier; Nocturne, Gaetane
Abstract : Objective: Peripheral ulcerative keratitis (PUK) is a rare but severe ocular complication of rheumatoid arthritis (RA). It can be considered as an ocular manifestation of rheumatoid vasculitis (RV). Our case series aimed to evaluate the efficacy of rituximab (RTX) for PUK occurring in patients with RA. Methods: Study population were patients with RA-associated PUK treated with RTX 1000 mg on days 1 and 15 at least once after the diagnosis. We identified patients referred to the rheumatology and ophthalmology departments of our hospital between February 2014 and June 2020. We also included patients referred by their specialist after being contacted through the Club Rhumatismes et Inflammation. Demographic data and clinical and biological features were retrospectively collected. Results: We included seven patients (three men and four women, median age 58 years). All but one had a long-standing RA with a median disease duration of 13.9 years (IQR 0–30.2). RA was erosive in six out of seven patients. All patients had rheumatoid factors and anticitrullinated peptides antibodies were positive in six of them. PUK was complicated by corneal perforation in three patients and required surgery. After a median follow-up of 29.8 months (IQR 5–75), corneal inflammation was controlled in all patients. PUK recurred in one patient, 8 months after a single infusion of RTX. 71% of the patients presented a good articular response. No patient developed other manifestations of RV. No serious adverse event related to RTX was observed. Conclusion: RTX appears to be an efficient and safe therapeutic option in the treatment of RA-associated PUK.